2017
DOI: 10.3390/economies5020020
|View full text |Cite
|
Sign up to set email alerts
|

Does FDI Really Matter to Economic Growth in India?

Abstract: Abstract:The main contribution of this article is to examine the productivity spillover effects from India's inward foreign direct investment (FDI), controlling for trade, in the framework of the cointegrated vector autoregression (CVAR). For this purpose, using the Solow residual approach the aggregate total factor productivity (TFP) in India is estimated to measure FDI-induced spillovers. The results show that the inflow of FDI to India indeed improves TFP growth through positive spillover effects. We also f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 35 publications
5
31
0
Order By: Relevance
“…This is, however, contrary to the conventional belief that exports increase productivity through learning by doing and/or exporting hypothesis. With regard to the negative impact of exports on TFP growth, our results lend support for the studies of Behera and Yadav (2019), Choi and Baek (2017), , Kim and Lin (2009), and Trejos and Barboza (2015). These studies provide a number of channels through which exports affect TFP negatively.…”
Section: Analysis Of the Long-run And Short-run Relationshipsupporting
confidence: 79%
See 1 more Smart Citation
“…This is, however, contrary to the conventional belief that exports increase productivity through learning by doing and/or exporting hypothesis. With regard to the negative impact of exports on TFP growth, our results lend support for the studies of Behera and Yadav (2019), Choi and Baek (2017), , Kim and Lin (2009), and Trejos and Barboza (2015). These studies provide a number of channels through which exports affect TFP negatively.…”
Section: Analysis Of the Long-run And Short-run Relationshipsupporting
confidence: 79%
“…The studies by Kim and Lin (2009) and Trejos and Barboza (2015) found that the impact of exports on productivity is conditional on the level of economic development, with trade having a positive effect on productivity across the developed countries, but it can have a negative impact across developing countries. On the other hand, Choi and Baek (2017) argued that Indian exports are dominated by primary industries such as unrefined (15% of total exports), gems and jewellery (13%), agricultural products (10%), cotton (10%) and cotton-based ready-made garments and accessories (6%). Such a composition of exports exerts a negative impact on TFP, which is primarily driven by technological change.…”
Section: Analysis Of the Long-run And Short-run Relationshipmentioning
confidence: 99%
“…Because FDI and trade are two important components of economic growth in Bangladesh, it is important to frame policies that promote growth and reduce the barriers for capital flows. Choi and Baek (2017) reported that FDI inflows lead to improve TFP growth in India through positive spillover effects. Using the ARDL technique, Ridzuan et al (2017) found that FDI inflows play an important role in increasing economic growth in Singapore over the period 1970-2013. In the other side, the relationship between domestic investment and economic growth has been reported by many empirical studies.…”
Section: Introductionmentioning
confidence: 99%
“…However, using the Granger causality tests, they find an inconclusive causality between foreign direct investment and economic growth in Botswana. Finally, Choi and Baek (2017) examine the productivity spill-over effects from inward foreign direct investment by controlling for trade, in the framework of the co-integrated vector auto-regression (CVAR) based on Solow residual approach of the aggregate total factor productivity in India. The results show that the inflow of FDI to India indeed improves total factor productivity growth through positive spill-over effects.…”
Section: Review Of Selected Literaturementioning
confidence: 99%